PREDICTION OF THE ROLE OF CURCUMINOIDS IN CURCUMA LONGA AS GSK-3 INHIBITORS ON TERTIER DENTIN GROWTH - Naila Robbaniyya Fithriyya; Hanifah Nur Syafa; Dwi Cinthya Financia; Nadya Elsa Cahyaningrum; Husni Rama Wijayanti; Haidy Lailatun Nabila; Salma Kaltsum Kayana; Ghaida Humaira Susilo Putri; Nurul Hasanah Tanjung; Pratiwi Nur Widyaningsih; Ryana Budi Purnama; Tirta Wardhana (Fakultas Kedokteran Universitas Jenderal Soedirman, 2021)
Caries is one of the most common oral diseases. Tertiary dentin regeneration has recently been developed as an alternative treatment for caries. Curcuminoids are known to have the ability to inhibit GSK-3β in the Wnt signalling pathway to accelerate the formation of reparative dentin. This study aimed to investigate curcuminoids as GSK-3β inhibitors in modulating tertiary dentin formation through the Wnt pathway. Insilico analysis has been carried out using an online database and software. Data collection is done through the Protein Data Bank https://www.rcsb.org/ dan PubChem https://pubchem.ncbi.nlm.here.gov/. The analysis of interactions between proteins and bioactive compounds through the STITCH website http://stitch.embl.de/ dan STRING https://string-db.org/.The results obtained that STK3 protein that binds to curcuminoids has a hippo signalling pathway that inhibits GSK-3β in the Wnt pathway. The study concludes that curcuminoids have the potential to accelerate the development of tertiary dentin.